Ampullary cancer: Evaluation of somatic and germline genetic alterations and association with clinical outcomes. Issue 9 (8th January 2019) - Wong, Winston; Lowery, Maeve A.; Berger, Michael F.; Kemel, Yelena; Taylor, Barry; Zehir, Ahmet; Srinivasan, Preethi; Bandlamudi, Chaitanya; Chou, Joanne; Capanu, Marinela; Varghese, Anna; Yu, Kenneth H.; et al.
Abstract: Background: Ampullary carcinoma (AC) is a rare gastrointestinal cancer. Pathogenic germline alterations (PGAs) in BRCA2 and potentially targetable somatic alterations (SAs) in ERBB2 and ELF3 have been previously described in AC. Memorial Sloan Kettering Cancer Center has implemented an opt‐in strategy for germline testing (GT) and somatic testing (ST) for patients with AC to further evaluate the spectrum of PGAs and SAs. Methods: Forty‐five patients with pathologically confirmed AC prospectively consented with the Memorial Sloan Kettering Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT) test (410‐468 genes). A subset of the cohort (23 of the 45 patients) also consented to GT with MSK‐IMPACT (76‐88 genes). Germline data for 21 of the remaining 22 patients who had not consented to GT were obtained in a de‐identified fashion without clinical correlation. Clinicopathologic features, treatment histories, and survival data for consenting patients were collected and analyzed. Results: Pancreaticobiliary, intestinal, and mixed features of the 2 types were the primary pathologic subtypes of AC identified in this cohort. No difference in median overall survival was found between pathologic subtypes. Eight of 44 patients (18%) were identified as harboring pathogenic mutations in BRCA2, ATM, RAD50, and MUTYH . In addition, this study found a wide spectrum of SAs in genes such as KRAS, MDM2, ERBB2, ELF3, and PIK3CA . Two patients in the cohort underwent SA‐targeted therapy, and 1 had a partial radiographic response. Conclusions: Mutations in multiple somatic and germline genes were identified in this cohort. Significantly, actionable targets were identified in the tumors, and broader testing for PGAs and SAs should be considered for all patients with AC. Abstract : Ampullary cancer is a rare malignancy for which actionable somatic findings are relatively common. Germline alterations also occur with some frequency, and both somatic and germline testing should be considered for all patients with this disease.